A Review of Japanese Ecological Anthropology on Central African Hunter-gatherers - Mitsuo Ichikawa (Revue d'ethnoécologie)
Contemporary hunter-gatherers in central Africa face similar problems concerning their culture and environment: destruction of the forests that have been accommodating their unique forest-based culture, influences of market economy and consumerism, and nature conservation initiatives that restrict their extractive activities in protected areas. In order to cope with these problems, it is important to understand their life and culture in local ecological settings, as well as in historical and wider economic and political contexts. I will describe here three approaches that have been taken and developed by Japanese ecological anthropologists to the study of central African hunter-gatherers. The three approaches are (1) cultural ecology, which describes the way the hunter-gatherers perceive, understand and utilize the forest environment, (2) historical ecology, which shows how they modify the forest through interacting with it, and (3) political ecology, which analyzes how the economic and political situation influences their relationship with the forest. I will then examine the implications of the results from these approaches for addressing the current problems faced by the central African forest hunter-gatherers and their environment.